Examining Institutional Practices and their effects on Student Success - Adebulehin, Aderinsola Michelle (Department of Social Development, 2019)
Given South Africa’s racialized history of access to education, redress efforts targeted at achieving equity in access to universities for students from across racial backgrounds have been well underway for over two decades now. More recently, within the higher education sector, ensuring that access translates into success has become a priority. Drawing on this concern, this research study looks into what constitutes success for previously excluded students at a historically white university. In addition, this research study examines the experiences of these students to uncover factors which contribute to either enabling or constraining their abilities to achieve this much sought after success. The analysis presented in this study arrived at the conclusion that institutional practices continue to entrench various forms of systematic exclusion which in turn significantly affect black students’ abilities to achieve success at a historically white university.